POTENSI SELADA LAUT Ulva lactuca SEBAGAI ANTIFUNGI DALAM PENGENDALIAN INFEKSI SAPROLEGNIA DAN ACHLYA PADA BUDIDAYA IKAN KERLING (Tor sp) - Zulfadhli Zulfadhli; Rinawati Rinawati (JURNAL PERIKANAN TROPIS, 2018)
This research aims to determine the effectivity of seaweeds extract (Ulva lactuca) as an antifungal in the control of kerling (Tor sp) infected with saprolegnia and achlya fungal. The research was conducted in May 2018 at the MIPA Laboratory, Syiah Kuala University and the Hatchery of the Faculty of Fisheries and Marine Sciences, Teuku Umar University. The research method was experimental with a completely randomized design (RAL), 3 treatments and 3 replications. The treatment given was immersion of kerling fish seeds infected with fungi in a solution of sea lettuce extract with the concentration of treatment namely: K (control) = 0 ppm, P1=5 ppm, P2=10 ppm, dan P3=15 ppm. Phytochemical test results showed that the content of bioactive compounds contained in ethanol extract of seaweed were alkaloids, steroids and phenolic/tannins. Ethanol extract of sea lettuce can inhibit the growth of Saprolegnia and Achlya in vitro by forming a clear zone of 5.7 mm (medium). The highest percentage of fish survival rate was in the treatment (P3) concentration of 15 ppm.